2022
DOI: 10.1093/stmcls/sxac038
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 and Lef1 Regulate the Fate and Behavior of Airway Glandular Progenitors in Response to Injury

Abstract: Cartilaginous airways of larger mammals and the mouse trachea contain at least 3 well-established stem cell compartments, including basal cells of the surface airway epithelium (SAE) and ductal and myoepithelial cells of the submucosal glands (SMG). Here we demonstrate that glandular Sox9-expressing progenitors capable of SAE repair decline with age in mice. Notably, Sox9-lineage glandular progenitors produced basal and ciliated cells in the SAE, but failed to produce secretory cells. Lef1 was required for gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…Thus, we conclude that glandular contribution to the airway surface repair can at least partially account for appearance of Krt14 on the injured surface epithelium. These observations are consistent with prior work demonstrating surface repair by glandular progenitors in mice and ferrets in vivo ( 8 , 9 , 24 , 25 ).…”
Section: Resultssupporting
confidence: 92%
“…Thus, we conclude that glandular contribution to the airway surface repair can at least partially account for appearance of Krt14 on the injured surface epithelium. These observations are consistent with prior work demonstrating surface repair by glandular progenitors in mice and ferrets in vivo ( 8 , 9 , 24 , 25 ).…”
Section: Resultssupporting
confidence: 92%
“…However, in the silica-treated group, basal cells were distributed not only on the basal layer but also on the upper layer, but their ectopic distribution was restored by treatment with the NLRP3 inflammasome inhibitor MCC950 (Figure 6 A). Furthermore, SOX2 and SOX9 are two pluripotency-associated stem/progenitor cell transcription factors that drive the proliferation and differentiation of airway epithelial basal cells following injury 51 - 53 . Our immunofluorescence results indicated that after stimulation with silica, most ectopic basal cells on the upper layer were positive for SOX2 (Figure 6 B, white arrows), with a significantly increased proportion of SOX2 + basal cells in the LSPC-derived airway epithelium (Figure 6 C).…”
Section: Resultsmentioning
confidence: 99%
“…The specific spatiotemporal distribution of SOX9 and SOX2 contributes to proper cell proliferation and differentiation, allowing lung development, repair and regeneration. In response to injury caused by smoking, SOX9 drives the generation of airway basal cells and leads to the repair of the mucociliary epithelium 52 , 53 . In bleomycin-induced lung injury, SOX2 regulates alveolar epithelial plasticity by inducing the emergence of progenitor-like cells, but continuous proliferation of SOX2 + cells disrupts alveolar structure, including septal rupture 90 .…”
Section: Discussionmentioning
confidence: 99%
“…DMEM was chosen for its simplicity because we hypothesized that tracheal explants can produce everything that they require for prolonged survival and repair after injury. F-medium was chosen because it is permissive for the survival of both epithelial and mesenchymal cells when used in colony formation efficiency (CFE) assays of airway basal cells that are grown on 3 T3-J2 fibroblasts ( 15 , 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of them were MMP9 and LAMA3 that are both associated with ECM deposition and remodeling and are upregulated in epidermal wound healing ( 25 , 26 ). We also assessed the expression of SOX9, a marker of airway SMG progenitors that have been previously shown to participate in SAE regeneration ( 15 , 27 , 28 ). As expected, all three of these targets were upregulated in both severely injured and moderately injured epithelia, with the level of upregulation corresponding to the level of injury ( Figure 6D ).…”
Section: Resultsmentioning
confidence: 99%